Legionella pneumophila in Rainwater on Roads - Ryota Sakamoto; Akira Ohno; Toshitaka Nakahara; Kazunari Satomura; Suketaka Iwanaga; Yuuichiro Kouyama; Fumiaki Kura; Naoyuki Kato; Kozo Matsubayashi; Kiyohito Okumiya; Keizo Yamaguchi (Emerging Infectious Diseases, 2009)
During rain, transient puddles form on roads, and this water is splashed into the air by moving vehicles. To determine whether this water contains Legionellapneumophila, we collected samples from roads. We found that L. pneumophila are abundant in these puddles, especially during warm weather.